Magnetic characteristics of nanocrystalline multiferroic BiFeO3 at low temperatures - Vijayanand, S.; Mahajan, Mangesh B.; Potdar, H. S.; Joy, Pattayil Alias (Physical Review B, 2009)
The magnetic characteristics of nanocrystalline BiFeO3 with average crystallite sizes of similar to 50 and similar to 100 nm are evaluated by studying the temperature and field dependence of magnetization at low temperatures. Different properties such as magnetization, coercivity, and remanence show evidence for changes in the magnetic properties associated with the phase transitions at low temperatures, reported from Raman studies. Detailed field-cooled and zero-field-cooled magnetization measurements show that the likely origin of the changes in the magnetic characteristics is from the changes in the domain structure.
Keywords: bismuth compounds; coercive force; crystallites; magnetic domains; magnetic transitions; Multiferroics; Nanostructured materials; Raman spectra; remanence

Origin of high room temperature ferromagnetic moment of nanocrystalline multiferroic BiFeO3 - Vijayanand, S.; Potdar, H. S.; Joy, Pattayil Alias (Applied Physics Letters, 2009)
Single phase nanocrystalline BiFeO3 of average crystallite size similar to 25 nm with very high magnetization at room temperature is synthesized by an autocombustion method. Magnetic measurements above room temperature show deviation between field cooled and zero field cooled magnetization below 645 K, the Neel temperature (T-N) of the bulk material, indicating intrinsic nature of ferromagnetism. However, observation of a broad magnetic transition above T-N of BiFeO3 and extended up to 800 K suggests the presence of Fe3O4 as a possible magnetic impurity phase. Evidence for the presence of Fe3O4 is obtained from detailed analysis of the powder x-ray diffraction pattern.
Keywords: bismuth compounds; Combustion synthesis; crystallites; ferromagnetic materials; high-temperature effects; magnetic impurities; Magnetic moments; Magnetisation; Multiferroics; Nanostructured materials; Neel temperature; X-ray diffraction

Polymer crystallization in the presence of ``sticky'' additives - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2009)
The effect of ``sticky'' additives (viz., those that have attractive interactions with the polymer) on polymer crystallization, has been investigated by dynamic Monte Carlo (DMC) simulations. Additive-polymer attractive interactions result in a slowing down of the polymer chain diffusivity in the melt state. Our results show that with increasing additive stickiness, polymer crystallinity decreases monotonically, and thinner crystallites form, viz., crystallization is inhibited by the presence of sticky additives. Unusually, the observed ``specific heat'' peak at the phase transition shows nonmonotonic behavior with additive stickiness, and exhibits a maximum for intermediate values of additive stickiness. While the origins of this unexpected behavior are not clear, we show that it correlates with a large interchange between crystalline and amorphous states of the monomers, in the vicinity of the additives. At this intermediate additive stickiness, we also find that crystallization follows a qualitatively different route-crystallinity shows a non-Avrami-like evolution, unlike the case at low or high additive stickiness.
Keywords: Additives; amorphous state; crystallisation; crystallites; Diffusion; Monte Carlo methods; polymer melts